ICAR: Intersection-based connectivity aware routing in vehicular ad hoc networks (2013)
In this paper, we propose an intersection-based connectivity-aware routing protocol (iCAR) for vehicular ad hoc networks (VANETs) to enable infotainment and interactive applications, as well as multi-hop Internet access in urban environments. iCAR is a novel protocol that takes into consideration real-time vehicular traffic information and the experienced packet delivery delay per road, in order to improve the routing performance by dynamically selecting roads with a guaranteed connectivity and a reduced delivery delay. This is achieved by deploying a microscopic view of vehicles location to proactively estimate roads connectivity and the minimum link lifetime per road. Detailed analysis and simulation-based evaluations show that iCAR significantly improves the network performance in terms of packet delivery ratio and end-to-end delay with a negligible cost of communication overhead. © 2013 IEEE.